On the weak limit of compact operators on the reproducing kernel Hilbert space and related questions - Saltan Suna (Analele Stiintifice ale Universitatii Ovidius Constanta: Seria Matematica, 2016)
By applying the so-called Berezin symbols method we prove a Gohberg- Krein type theorem on the weak limit of compact operators on the non- standard reproducing kernel Hilbert space which essentially improves the similar results of Karaev [5]: We also in terms of reproducing kernels and Berezin symbols investigate the structure of invariant subspaces of compact operators.